In-center Nocturnal Hemodialysis Reduced the Circulating FGF23, Left Ventricular Hypertrophy, and All-Cause Mortality: A Retrospective Cohort Study - Kang, Meizi; Chen, Jing; Liu, Lingling; Xue, Cheng; Tang, Xiaojing; Lv, Jiayi; Fu, Lili; Mei, Changlin; Mao, Zhiguo; Liu, Yawei; Dai, Bing (Frontiers in Medicine, 2022)
Fibroblast growth factor 23(FGF23) is the most important biomarker and pathogenic factor in Chronic Kidney Disease-Mineral and Bone disorder (CKD-MBD). In the moderate and severe stages of chronic renal failure, abnormally elevated circulating FGF23 can lead to some complications including myocardial hypertrophy, which is positively correlated with the all-cause mortality. However, the circulating FGF23 level of different hemodialysis modalities, the underlying essential regulatory factors and potential clinical benefits remain to be elucidated. In this retrospective cohort study, 90 in-center nocturnal hemodialysis (INHD) and matched 90 conventional hemodialysis(CHD) patients were enrolled. The complete blood count, intact FGF23(iFGF23), calcium, phosphorus, PTH, other biochemical and echocardiographic parameters of INHD and CHD patients were collected and analyzed at 1-year follow-up. The all-cause mortality was recorded during the 7 years follow-up. Furthermore, the regulatory factors of iFGF23 and association with echocardiographic parameters and mortality were investigated by multivariate regression. The levels of iFGF23 and serum phosphate in patients undergoing INHD were significantly lower than that in patients undergoing CHD. The left ventricular volume index (LVMI) in INHD patients was significantly attenuated and positively correlated with the drop of the serum iFGF23. The INHD group had reduced all-cause mortality compared to CHD group. Multivariate analysis showed that iFGF23 was positively correlated with serum calcium, serum phosphorus, calcium-phosphate product. Calcium-phosphate product is an independent determining factor of serum iFGF23. Compared with CHD group, INHD group presented with significant reduced circulating iFGF23 level which was closely associated with attenuation of left ventricular hypertrophy, but INHD reduced all-cause mortality in a FGF23 independent manner.